Suplementação de cromo ou L-carnitina para potras Mangalarga Marchador submetidas a um programa de condicionamento - Mayara Gonçalves Fonseca (2014)
The present study aimed to evaluate the effect of dietary supplementation of chelated chromium (Cr) or L-carnitine (LC) on fitness and on morphometry of muscle fibers of Mangalarga Marchador fillies. Thirteen fillies were divided into three groups: Cr (n=4, 10 mg/day of chelated chromium); LC (n=4; 10 g/day of L-carnitine) and control (n=5; without supplementation). The animals were exercised on a treadmill and automatic walker on alternate days, from Tuesday to Sunday, during 42 days. In day 7 (Test 1) , 21 (Test 2) and 42 (Test 3) marcha tests were performed on a treadmill with 5 min warming (1.7 m/s) followed by 30 minutes of marcha gait (3.5 m/s and 3 % slope). We evaluated the heart rate (HR), blood lactate (Lac), blood glucose (Glu) and serum triglycerides (Trigl) before exercise, every 5 minutes during the three marcha tests and during the recovery of tests 1 and 3. Gluteus medius muscle biopsies were performed in the first and sixth weeks of conditioning program. The samples were subjected to histochemical mATPase staining and were determined the proportion of the type fibers per field examined (% N), the average of the cross-sectional area (ACSA) and the relative total area (RTA%) occupied by each type muscle fiber. There was no effect (P>0.05) of Cr of LC supplementation at HR, Lac, Glu or Trigl during the tests or in the recovery stage. 21 days of conditioning program (Test 2) have decreased (P<0.05) the HR and Lac measured during the marcha tests, but there was no effect of conditioning (P>0.05) in the recovery stage. Glu and Trigl was not affected by conditioning program (P>0.05). There was no changes (P>0.05) in (% N) of fibers of type I , IIA and IIX . After conditioning, the Cr and LC increased (P<0.05) the ACSA of type I fibers, while the LC also caused an increase (P<0.05) in ACSA of type IIA fibers and Cr caused a reduction (P<0.05) in ACSA of type IIA fibers. There was an increase (P<0.05) in the RTA% of type I fibers after the conditioning period. The aerobic conditioning combined with Cr or LC supplementation results in morphological changes of muscle fibers by increasing their oxidative metabolic properties, but does not change the performance of the MM fillies subjected to marcha tests on a treadmill.